The Effect of Virtual Laboratories on Students' Science Process Skills: A Literature Review 2016-2025 - Hayatun Novi Aulia; Fadillah Deswita Sari; Lindawati Lindawati; Gunawan Gunawan; Nina Nisrina (Indonesian Journal of STEM Education, 2025)
Science process skills are essential abilities in science learning because they help students understand scientific concepts and conduct scientific activities systematically. However, limitations in time, laboratory equipment, and materials often become obstacles in implementing practical activities in schools. Previous studies have reported the effectiveness of virtual laboratories in improving science process skills; however, these findings remain fragmented and lack a comprehensive synthesis across different educational contexts. This study aims to analyze the effect of virtual laboratory use on students’ science process skills through a literature review. The study employed a systematic literature review of articles published between 2016 and 2025, obtained from Google Scholar using keywords such as virtual laboratory, laboratorium virtual, and science process skills. A total of 15 articles were selected based on inclusion criteria, including relevance to the research topic, empirical research design, and availability of full-text articles. The results show that virtual laboratories consistently have a positive impact on improving students’ science process skills across various educational levels. The findings also indicate that the effectiveness of virtual laboratories is influenced by the learning models applied, particularly inquiry-based approaches, and is reflected in moderate to high improvement categories (e.g., N-Gain scores). In addition, virtual laboratories offer advantages in terms of flexibility, accessibility, and efficiency in conducting experiments. In conclusion, virtual laboratories are effective learning media that can enhance students’ science process skills and serve as an alternative or complement to conventional laboratories in science learning.